Software as a Service based Project Management System - Aishwarya Madhav Pimparkar,; Amruta Gopinath Shinde,; Shivani Santosh Adale,; Dr. Date A.R,; Dr. Divekar S.N, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research paper presents the design and implementation of a SaaS-based Project Management System, built using Next.js and MongoDB, to facilitate effective project planning, execution, and real-time collaboration. The study details the integration of modern web technologies with scalable, cloud-native architecture, ensuring seamless user experiences and robust data management. By addressing the limitations of traditional project management tools, our proposed system enhances task organization, resource allocation, and progress tracking. The approach leverages advanced features such as server-side rendering, dynamic routing, and flexible schema design to deliver a comprehensive solution that meets the growing demands of global teams and remote work environments. In this paper, we elaborate on the technical nuances and human-centric design principles that underpin the system's development. Emphasis is placed on the balance between technical precision and usability, ensuring that the system remains accessible to non-technical stakeholders while providing the robust functionality required by project managers and IT professionals. Through detailed analysis and empirical evaluations, the research demonstrates the system’s capacity to improve productivity and operational efficiency in diverse business contexts.
Keywords: Project Management System; Next.js; MongoDB; Cloud Computing; Real-time Collaboration; Agile Development; Scalable Architecture; User-Centric Design; Software-as-a-Service; System Integration; Web-based Application